Competition in Germany's minute reserve power market: An econometric analysis - Justus Haucap; Ulrich Heimeshoff; Dragan Jovanovic (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2012)
The German reserve power market was subject to important regulatory changes in recent years. A new market design was created by synchronization and interconnection of the four control areas. In this paper, we analyze whether or not the reforms led to lower prices for minute reserve power (MRP). In contrast to existing papers, we use a unique panel dataset to account for unobserved heterogeneity between the four German regional markets. Moreover, we control for endogeneity by using weather data as instruments for electricity spot market prices. We find that the reforms were jointly successful in decreasing MRP prices leading to substantial cost savings for the transmission system operators.
Keywords: C33; C36; L59; L94; 330; Competition; Frequency Control; Minute Reserve Power; Regulation; Productive Efficiency; Welfare